Accurate and Robust Calibration of the Uniform Affine Transformation Between Scan-Camera Coordinates for Atom-Resolved In-Focus 4D-STEM Datasets - Ning, Shoucong (CAMBRIDGE UNIV PRESS, 2022)
10.1017/S1431927622000320